2021
DOI: 10.3390/antibiotics10030320
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcus aureus (MRSA) Clonal Replacement in a Malaysian Teaching Hospital: Findings from an Eight-Year Interval Molecular Surveillance

Abstract: Periodical surveillance on nosocomial pathogens is important for antimicrobial stewardship and infection control. The first methicillin-resistant Staphylococcus aureus (MRSA) molecular surveillance in Hospital Canselor Tuanku Muhriz (HCTM), a Malaysian teaching hospital, was performed in 2009. The dominant clone was identified as an MRSA carrying SCCmec type III-SCCmercury with ccrC and sea+cna toxin genes. In this study, we report the findings of the second HCTM MRSA surveillance carried out in 2017, after an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In 2018, a study reported the detection of MRSA spa type t032 from the community nasal swabs of healthy adults (11.1%, 2/18) in the same eastern coast state of Malaysia as this study (i.e., Terengganu), suggesting that this clone is likely circulating in communities without exposure to healthcare settings [ 47 ]. Recently, a high prevalence of spa type t032 in hospitalized patients was reported from two studies conducted in central Malaysia (72.1%, 160/222) and in Terengganu (39.3%, 35/89) [ 27 , 48 ]. Our preliminary WGS study of 62 clinical MDR-MRSA isolates revealed that the EMRSA-15 (ST22-SCC mec IV [2b]) clone (67.7%) and spa type t032 (50%) were indeed predominant (67.7%) in our local scenario [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a study reported the detection of MRSA spa type t032 from the community nasal swabs of healthy adults (11.1%, 2/18) in the same eastern coast state of Malaysia as this study (i.e., Terengganu), suggesting that this clone is likely circulating in communities without exposure to healthcare settings [ 47 ]. Recently, a high prevalence of spa type t032 in hospitalized patients was reported from two studies conducted in central Malaysia (72.1%, 160/222) and in Terengganu (39.3%, 35/89) [ 27 , 48 ]. Our preliminary WGS study of 62 clinical MDR-MRSA isolates revealed that the EMRSA-15 (ST22-SCC mec IV [2b]) clone (67.7%) and spa type t032 (50%) were indeed predominant (67.7%) in our local scenario [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent report from 2016 to 2017 of MRSAs isolated from Kelantan, a state located at the north of Peninsular Malaysia just across the border from Thailand, revealed that majority of MRSA isolates were ST22 (68.2%), followed by ST239 (29.5%) [45]. Another molecular surveillance in a teaching hospital, Hospital Canselor Tuanku Muhriz (HCTM), conducted in 2017, reported clonal replacement of the previous dominant MRSA clone of SCCmec type III-SCCmercury (these clones were also found to carry sea+cna) with SCCmec type IV (which carried seg + sei) after an eight-year interval from the first molecular surveillance carried out in the hospital in 2009 [44,46]. This clonal replacement phenomenon has been observed in many countries, such as Singapore, the United States, and Germany [25,47,48].…”
Section: Malaysiamentioning
confidence: 99%
“…Most studies involving Malaysian clinical isolates inferred that ST239-SCC mec type III is the most circulating clone in the hospital setting ( 10 , 24 , 29 , 30 , 33 , 37 , 38 ). ST239-III is a single-locus variant of ST8 found to be the predominant clone in most Asian countries, including from neighbouring countries such as Indonesia, Lao People’s Democratic Republic, Vietnam and Thailand ( 39 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving MRSA clinical isolates in 2014 and 2015, ST22-IV was the most prevalent clone identified instead of ST239-III ( 23 ). However, a more recent study found that SCC mec IV and t032 predominated the MRSA isolates in 2017 ( 24 ). Based on the spa -typing database ( https://www.spaserver.ridom.de/ ), the MLST of the t032 is found to be ST22.…”
Section: Introductionmentioning
confidence: 99%